2010
DOI: 10.1063/1.3523264
|View full text |Cite
|
Sign up to set email alerts
|

Understanding anomalous delays in a model of intracellular calcium dynamics

Abstract: In many cell types, oscillations in the concentration of free intracellular calcium ions are used to control a variety of cellular functions. It has been suggested [16] that the mechanisms underlying the generation and control of such oscillations can be determined by means of a simple experiment, whereby a single exogenous pulse of inositol trisphosphate (IP 3 ) is applied to the cell.However, more detailed mathematical investigations [6] have shown that this is not necessarily always true, and that the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Wechselberger [238] extends the theory of canards to such systems and Harvey et al [99] use these results to study models of intracellular calcium dynamics.…”
Section: Mmos: Bringing Together Theory and Datamentioning
confidence: 99%
“…Wechselberger [238] extends the theory of canards to such systems and Harvey et al [99] use these results to study models of intracellular calcium dynamics.…”
Section: Mmos: Bringing Together Theory and Datamentioning
confidence: 99%
“…Excitability of neurons [18,29,52] and networks are prime examples of transient dynamics, especially as responses to brief or non-stationary time-varying inputs. Recent developments in canard theory [26,63,64] have provided a new direction for understanding these transient dynamics that are modelled as nonautonomous multiple time-scale systems. It is well known that a nonautonomous system can be viewed as an extended autonomous system by increasing the phase space dimension by one.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a canard mechanism was identified that leads to transient dynamics in multiple time-scales systems [26,41,44,64]. Canards are exceptional solutions in singularly perturbed systems which occur on boundaries of regions corresponding to different dynamic behaviours.…”
Section: Motivationmentioning
confidence: 99%
“…In a neighborhood of the fold surface L or a folded node, the asymptotic error estimates were O(ε 2/3 ) [30,50] and O(ε 1/2 ) [9,62], respectively. Our work also adds to the currently scarce supply of examples of canard-induced MMOs in systems with more than two slow variables [22,23]. In both the 3-fast/1-slow and 1-fast/3-slow analyses, the underlying geometry influences the bursting through a combination of local and global mechanisms.…”
Section: Delayed Hopf Bifurcation and Tourbillonmentioning
confidence: 99%
“…Such timescale splittings have been used to effectively explain neuronal dynamics [17,18,43,44,64] and intracellular calcium dynamics [22,23]. This section also adds to the currently sparse literature of examples dealing with systems that have more than two slow variables [22,23,63]. The 1-fast/k-slow approach has been applied to 3D reductions of (2.2) in which k = 2.…”
Section: The ε-Viewpointmentioning
confidence: 99%